Mental health of women living with HIV and its impact on child development in Andhra Pradesh, India. Issue 4 (2nd October 2021) - Satyanarayana, Veena A.; Burroughs, Hadley R.; Heylen, Elsa; Yadav, Kartik; Sinha, Sanjeev; Nyamathi, Adeline; Ekstrand, Maria L.
ABSTRACT: Global literature examining the association between mental health of women living with HIV (WLWH) and child development is scarce. In this study, we examined the relationship between mothers' mental health and their children's social development outcomes 6 months later. Data for these analyses come from several waves of interviews of 600 WLWH in the South Indian state of Andhra Pradesh, India. These women were enrolled in a 2 × 2 factorial clinical trial designed to assess the impact of food supplementation and nutrition education, both in addition to ASHA support, on adherence to ART and improved health outcomes for the women and one of their children. They were assessed on food security, stigma, social support, quality of life, depressive symptoms and child development outcomes. Results of longitudinal GEE regression analysis indicate that mother's depressive symptoms were significantly negatively associated with child's social quotient 6 months later. These findings have important implications for targeted health interventions, integrating mental health, both for WLWH and their children in India.